AB0743 Low rates of major adverse cardiac events, malignancies, and serious infections in patients with psoriasis and psoriatic arthritis treated with apremilast for ≥156 weeks: pooled analysis from the esteem and palace 1-3 phase 3 trials. (15th June 2017) - Kavanaugh, A; Augustin, M; Lespessailles, E; Papp, KA; Paris, M; Chen, R; Gladman, DD; Pariser, DM; Peris, K
Abstract : Background: Apremilast (APR), an oral PDE4 inhibitor, was effective in phase 3, randomized, placebo (PBO)-controlled trials assessing treatment of moderate to severe plaque psoriasis (ESTEEM 1 and 2) and psoriatic arthritis (PsA; PALACE 1–3). Objectives: We report incidence of MACE, malignancies, and serious infections (SIs; opportunistic and non-opportunistic) in pts receiving APR 30 mg BID (APR30) for ≥156 wks in a pooled analysis of these studies. Methods: Incidence rates and exposure-adjusted incidence rates (EAIR)/100 pt-yrs of MACE, malignancies, SIs, and serious opportunistic infections (SOIs) are reported for 0 to 16 wks, 0 to ≤52 wks, and the APR-exposure period (0 to ≥156 wks) for pts receiving APR30 any time during the studies, through February 2015; ∼30% (n=575) of pts received >3 yrs (>156 wks) of APR exposure. Results: 2, 242 pts were included in the safety analysis for 0 to 16 wks (PBO n=913, pt-yrs exposure [py]=260.2; APR30 n=1, 329, py=377.8); 1, 905 pts received APR30 during the APR-exposure period, representing 3, 527.5 py; exposure during 0 to ≤52 wks was 1, 524.5 py. At baseline 64.2% of PsA pts (PALACE 1–3) in the APR30 group were receiving concomitant DMARDs (including methotrexate). Incidence of MACE with APR30 was low and comparable to PBO during 0 to 16 wks. During 0 to ≤52 wks and the APR-exposure period, incidence of MACE (EAIR/100 pt-yrs) remained low (Table). Incidence rates (EAIR/100 pt-yrs) of hematologic malignancies, non-melanoma skin cancers, and solid tumors were similar with PBO (0.0, 1.2, 0.4) and APR30 (0.0, 1.3, 0.3) during 0 to 16 wks; incidence rates remained low during 0 to ≤52 wks and the APR-exposure period (Table). During 0 to 16 wks, the overall rate of infections (serious and non-serious) was low and comparable between pts receiving PBO (20.6%) and APR30 (24.8%). The overall rate of infections (serious and non-serious) was 42% during 0 to ≤52 wks and comparable to rates during the PBO-controlled period (0 to 16 wks); the majority of reported infections (URTI, nasopharyngitis, sinusitis) were not serious. During the PBO-controlled period (0 to 16 wks), rates of SIs with APR30 were low and comparable to PBO; no SOIs were reported. During 0 to ≤52 wks, the overall rate of SIs was low (0.6%; EAIR/100 pt-yrs: 0.7). The rate of SIs remained low (1.8%; EAIR/100 pt-yrs: 1.0) during the long-term cumulative APR-exposure period (0 to ≥156 wks) (Table). No clustering of any particular event was noted with respect to SIs; most events occurred in only 1 pt. No clinical reactivation of tuberculosis was reported with long-term APR30 exposure (0 to ≥156 wks). The rate of marked hematologic abnormalities remained low with long-term APR exposure. Conclusions: Incidence of MACE, malignancies, and SIs was low in pts with psoriasis and PsA receiving APR30 for ≥156 wks. No new safety signals or SOIs were observed over time with APR30. Disclosure of Interest: A. Kavanaugh Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, and UCB, M. Augustin Consultant for: AbbVie, Almirall, Amgen, Biogen, Boehringer Ingelheim, Celgene Corporation, Centocor, Eli Lilly, GSK, Janssen-Cilag, LEO Pharma, Medac, Merck, MSD, Novartis, Pfizer, UCB, and XenoPort, Speakers bureau: AbbVie, Almirall, Amgen, Biogen, Boehringer Ingelheim, Celgene Corporation, Centocor, Eli Lilly, GSK, Janssen-Cilag, LEO Pharma, Medac, Merck, MSD, Novartis, Pfizer, UCB, and XenoPort, E. Lespessailles Grant/research support from: Amgen, Celgene Corporation, Eli Lilly, and Novartis, Speakers bureau: Amgen, Celgene Corporation, Eli Lilly, and Novartis, K. Papp Grant/research support from: AbbVie, Allergan, Amgen, Anacor, Astellas, Baxalta, Biogen-Idec, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene Corporation, Dermira, Dow Pharma, Eli Lilly, Galderma, Genentech, Glenmark, GSK, Janssen, Kyowa Hakko Kirin, LEO Pharma, MedImmune, Merck, Merck Serono, Mylan, Novartis, Pfizer, Regeneron, Roche, Sanofi-Aventis, Stiefel, Takeda, UCB, and Valeant, Consultant for: AbbVie, Akros, Allergan, Amgen, Anacor, Astellas, AstraZeneca, Baxalta, Baxter, Biogen-Idec, Boehringer Ingelheim, Bristol-Myers Squibb, Can-Fite BioPharma, Celgene Corporation, Celtic, Cipher, Dermira, Dow Pharma, Eli Lilly, Formycon, Forward Pharma, Funxional Therapeutics, Galderma, Genentech, Genexion, Glenmark, GSK, Janssen, Kyowa Hakko Kirin, LEO Pharma, Lypanosys, MedImmune, Merck, Merck Serono, Mitsubishi Pharma, Mylan, Novartis, Novommune, Pan Genetics, Pfizer, Regeneron, Roche, Sanofi-Aventis, Stiefel, Sun Pharma, Takeda, UCB, Valeant, Vertex, and Xoma, M. Paris Employee of: Celgene Corporation, R. Chen Employee of: Celgene Corporation, D. Gladman Grant/research support from: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, and UCB, D. Pariser Grant/research support from: Abbott Laboratories, Amgen, Astellas Pharma US, Asubio Pharmaceuticals, Basilea Pharmaceutical, Celgene Corporation, Dow Pharmaceutical Sciences, Eli Lilly, Galderma Laboratories, Graceway Pharmaceuticals, Intendis, Johnson & Johnson, Novartis Pharmaceuticals, Novo Nordisk A/S, Ortho Dermatologics, Photocure ASA, Stiefel Laboratories, and Valeant Pharmaceuticals, K. Peris Consultant for: Eli Lilly, LEO Pharma, MEDA, and Roche